Handbook of home language maintenance and development social and affective factors - Schalley, Andrea C., 1972-; Eisenchlas, Susana A. (Handbooks of applied linguistics ;, 2020)
Even a cursory look at conference programs and proceedings reveals a burgeoning interest in the field of social and affective factors in home language maintenance and development. To date, however, research on this topic has been published in piecemeal fashion, subsumed under the more general umbrella of 'bilingualism'. Within bilingualism research, there has been an extensive exploration of linguistic and psycholinguistic perspectives on the one hand, and educational practices and outcomes on the other. In comparison, social and affective factors - which lead people to either maintain or shift the language - have been under-researched. This is the first volume that brings together the different strands in research on social and affective factors in home language maintenance and development, ranging from the micro-level (family language policies and practices), to the meso-level (community initiatives) and the macro-level (mainstream educational policies and their implementation). The volume showcases a wide distribution across contexts and populations explored. Contributors from around the world represent different research paradigms and perspectives, providing a rounded overview of the state-of-the-art in this flourishing field.